Development of Financial Literacy and Anti-Corruption Education in Primary Schools Through Storytelling Activities - Maya Kuswaty (Universitas Sebelas Maret, 2019)
Financial literacy and anti-corruption education are two interrelated entities. The deeper meaning when someone already has the ability to understand financially, must be accompanied by the knowledge of bad practices from financial crime. Call it a form of corruption crime that is currently rampant. Strangely this is sometimes done by those who already understand and understand financial material. Unfortunately, it has only not been able to fortify itself from the tricks of deception money and its mortal pleasures. If left unchecked it will certainly be a dark tale of all time for the next generation of the nation. Therefore, it is very important to turn the tale into a good tale of travel in fortifying itself from bad practices such as corruption crimes and the like. The research method in this study was to study descriptively the development of financial literacy and anti-corruption education in elementary schools through storytelling activities. Primary school is a strategic educational unit to instill anti-corruption values. This is supported by the characteristics of students in concrete operational categories and the golden age of establishing a strong identity through fun activities such as storytelling activities. Storytelling activities are considered effective in instilling anti-corruption values with light language for children without reducing the essence of the expected value.